(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Due to the fact that it breaks down into acrylamide over time, polyacrylamide is one of the most important sources of acrylamide in soil. As a strategy for bioremediation, the breakdown of acrylamide by the action of microbes has seen a gradual but consistent increase in attention all over the world. A previously isolated molybdenum-reducing bacterium with amide-degrading capability was further identified on significant parameters contributing to optimized growth on acrylamide using a two-level factorial design in this study. The two-level factorial design was adopted in the screening of five independent factors influencing the growth of the bacterium on acrylamide. These factors include pH, temperature, incubation time, acrylamide concentration and glucose concentration. The two-factor factorial design was successful in finding important contributing parameters in the growth of this bacterium on acrylamide, which were acrylamide concentration, pH and incubation time (p<0.05) that can be further optimized using RSM in future works. The important contributing factors or parameters were analysed using ANOVA, Pareto’s chart and perturbations plot and other diagnostic plots. The diagnostic plots such as half-normal, Cook’s distance, residual vs runs, leverage vs runs, Box-Cox, DFFITS, DFBETAS all supported the two-level factorial conclusion. This study was carried out using an acrylamide range well within the range reported to be tolerated by most acrylamide-degrading microorganisms. Incubation time is an expected result since longer incubation time allows more growth and incubation time ranging from two to five days for optimized growth has been reported in many acrylamide-degrading microorganisms. Most of the acrylamide-degrading microorganisms grow well in near-neutral conditions, of which the results obtained in this study conforms to the published literature trends.